Purification of the influenza hemagglutinin glycoprotein and characterization of its carbohydrate components. - Collins, J K (1978)
Hemagglutinin from influenza A/PR8 virus was purified after treatment of the virus with sodium deoxycholate followed by extraction with tri-n-butyl phosphate. This fully disrupted the virus while preserving hemagglutinating activity. The hemagglutinin was obtained in the form of small aggregates that could be separated from other viral components. Purified hemagglutinin was hydrolyzed to determine carbohydrate composition and digested with Pronase to analyze oligosaccharide structures. Sugars present in the hemagglutinin were galactose, mannose, fucose, and glucosamine in molar rates of about 6:11:2:5, and these comprised 16% of the hemagglutinin glycoprotein. Oligosaccharides obtained from virus included a major component of a molecular weight of 2,800, composed of glucosamine, galactose, mannose, and fucose, and a minor heterogenous component of a molecular weight of 1,500 to 2,000, containing predominantly mannose. The 2,800-molecular-weight oligosaccharide was a constituent of the hemagglutinin, and treatment of this large oligosaccharide with specific exo-glycosidases demonstrated the presence of terminal galactose and fucose and allowed the deduction of a general structure for this component.